Research on the Mining of Intangible Cultural Heritage Digital Resources in the Manual Online Teaching System of Preschool Education. (23rd April 2022) - Jun, Zhao; Li, Xingping
Abstract : Our country's international status as a cultural power has been further enhanced, and the protection of intangible cultural heritage containing the essence of traditional culture is also gradually being carried out. In addition, with the rapid development of the digital environment, the public's cultural needs continue to grow, and the contradiction between the supply and demand of public digital cultural services continues to intensify. Converting intangible cultural heritage into digital form for protection and providing resource services for the public has become an important trend in the protection and inheritance of intangible cultural heritage at home and abroad, and it is also an inevitable requirement to solve the contradiction between supply and demand. Improving public cultural services is one of the key projects. At present, our country's research and practice of intangible cultural heritage digitization and services are also in progress, but there is no research on intangible cultural heritage digital resource services and system construction from the perspective of information service elements. Based on the digital resource service of intangible cultural heritage, the manual course is one of the main skill courses for preschool education majors. At this stage, the short class hours of manual courses, the lack of class hours, the low utilization rate of teaching materials, and the disconnection between the content and the needs of the kindergarten are all problems that need to be solved at present. Just relying on cross-references between schools, the manual knowledge and skills mastered by graduates are not comprehensive enough to complete the manual tasks assigned by the kindergarten. This paper implements the concept of intangible cultural heritage and hopes that by studying the manual knowledge and skills that today's kindergarten teachers need to possess, the content of existing manual courses can be adjusted in a targeted manner, so that the electronic culture dissemination of manual curriculum resources for preschool education is more reasonable, meeting the requirements of kindergarten teachers in terms of manual knowledge and skills.